In Vitro Anti Cancer Properties Of Thiadiazole Coumarin Derivatives Against Colon Cancer - Furqan Faisal, Sarah (2019)
Thiadiazole coumarin derivatives have been shown to be promising anti-cancer agents. In this study, five different thiadoazole coumarin derivatives (TCDs) were studied for their anticancer activity towards colorectal, breast and lung carcinoma. The TCDs {(OCH3-TC 1), (H3CO-TC 2), (H3CO-TC 3), (Br-TC 4), & (OH-TC)} are different in their structures. The compounds were tested for two important pathways of carcinogenesis namely angiogenesis and apoptosis. Angiogenesis is a process of new blood vessel development which is crucial for neoplastic tissues to obtain nourishment for their growth and metastasis.